Strongly minimal Jonsson sets and their properties - Yeshkeyev, A.R. (Ye.A.Buketov Karaganda State University Publ., 2015)
This article introduced and considered the Johnson sets and their fragments. And respectively was considered strongly minimal Jonsson sets. On this basis, introduced the concept of the independence of special subsets of existentially closed submodel of the semantic model. The notion of independence leads to the concept of base and further we develop technique for Jonssonien analog of theorem on uncountable categoricity.
Қатты минималды йонсондық жиындар жəне олардың қасиеттері
Сильно минимальные йонсоновские множества и их свойства
Keywords: Johnson sets; thoery T, Johnson theory; semantic model